2020
DOI: 10.1136/bmjopen-2019-031208
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of the 2016 United States presidential election and the subsequent sex ratio at birth in Canada: an ecological study

Abstract: ObjectivesThe sex ratio at birth (proportion of boys to girls) generally shows slight male preponderance but may decrease in response to societal stressors. Discrete adverse events such as terrorist attacks and disasters typically lead to a temporary decline in the sex ratio 3–5 months later, followed by resolution over around 5 months thereafter. We hypothesised that the unexpected outcome of the 2016 US presidential election may have been a societal stressor for liberal-leaning populations and thereby precip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 23 publications
3
4
0
Order By: Relevance
“…Our findings are inline with the hypothesis that COVID-19 stress would result in SRB decline ( Abdoli, 2020 ), driven by the Trivers-Willard hypothesis which posits that adverse environmental conditions can lower the ratio of males to females ( Trivers & Willard, 1973 ). Our findings are also consistent with studies that have reported a transient SRB decline 3–5 months following unexpected events which stressed populations acutely ( Calleja, 2020 ; Grech, 2015a ; Grech, 2015b ; Masukume et al, 2017 ; Retnakaran & Ye, 2020 ). A sex ratio at birth of less than 0.5 has also been observed in the 3–5 months following the July 2011 Norway attacks, the December 2012 Sandy Hook Elementary School shooting, and the October 2017 assassination of investigative journalist Daphne Caruana Galizia ( Calleja, 2020 ; Grech, 2015b ).…”
Section: Discussionsupporting
confidence: 93%
“…Our findings are inline with the hypothesis that COVID-19 stress would result in SRB decline ( Abdoli, 2020 ), driven by the Trivers-Willard hypothesis which posits that adverse environmental conditions can lower the ratio of males to females ( Trivers & Willard, 1973 ). Our findings are also consistent with studies that have reported a transient SRB decline 3–5 months following unexpected events which stressed populations acutely ( Calleja, 2020 ; Grech, 2015a ; Grech, 2015b ; Masukume et al, 2017 ; Retnakaran & Ye, 2020 ). A sex ratio at birth of less than 0.5 has also been observed in the 3–5 months following the July 2011 Norway attacks, the December 2012 Sandy Hook Elementary School shooting, and the October 2017 assassination of investigative journalist Daphne Caruana Galizia ( Calleja, 2020 ; Grech, 2015b ).…”
Section: Discussionsupporting
confidence: 93%
“…This suggests that the SRB decline in England and Wales in June 2020 was not coincidental but rather was being driven by a common factor that simultaneously affected different continents and hemispheres. The finding is consistent with studies that found a transient reduction in SRB 3–5 months after unanticipated occurrences that stressed populations ( Calleja, 2020 ; Catalano et al, 2006 ; Grech, 2015 ; Retnakaran & Ye, 2020 ). As previously mentioned, the unanticipated onset of the COVID-19 pandemic was identified as a substantial population stressor, and it is known that such significant stressors can induce an SRB decrease, hence it is improbable that the June 2020 SRB dip in England and Wales was a random occurrence.…”
Section: Discussionsupporting
confidence: 92%
“…The increases or decreases have been noted to occur within two distinct time windows. The first window is 3–5 months after sudden and unanticipated stressful events such as terrorist attacks ( Bruckner, Catalano & Ahern, 2010 ), the death of a well-known public person ( Grech, 2015 ), or unexpected national election results ( Retnakaran & Ye, 2020 ). This first window is linked to a disproportionate pregnancy loss of male fetuses, which is reflected in a lower SRB a few months after the stressful event.…”
Section: Introductionmentioning
confidence: 99%
“…Three months after the COVID-19 pandemic was declared, a decline in the SRB was noted in South Africa in June 2022 (Masukume et al 2022), which is similar to the transient decline in SRB observed in this study in June 2020. This is consistent with studies that found a transient reduction in SRB 3-5 months after unanticipated occurrences that stressed populations (Calleja 2020;Catalano et al 2006;Grech 2015;Retnakaran & Ye 2020).…”
Section: Comparison With Other Studiessupporting
confidence: 92%
“…The increases or decreases have been noted to occur within two distinct time windows. The first window is 3-5 months after sudden and unanticipated stressful events such as terrorist attacks (Bruckner et al 2010), the death of a well-known public person (Grech 2015), or unexpected national election results (Retnakaran & Ye 2020). This first window is linked to a disproportionate pregnancy loss of male fetuses, which is reflected in a lower SRB a few months after the stressful event.…”
Section: Introductionmentioning
confidence: 99%